Influence of Filler Materials on Pinned Joints of Woven Glass Fiber Reinforced Epoxy Composites - Harsha, H.M.; Murugesh, M.C.; Bharath, K.N. (Journal of Composites and Biodegradable Polymers, 2013)
Fiber reinforced composite materials have been gaining wide application in aircraft submarine and spacecraft constructions, to strengthen bridges and other civil engineering structures. Joints are formed using mechanical fasteners and load sharing in these joints depends on the number, size, and material of the bolts and the stiffness of the joining members. Therefore, suitable revealing methods for the failure strength would help in selecting the appropriate joint size in a given application. The objective of the present work is to determine the bearing or failure load of filler added woven glass fiber/epoxy composites through single and double serial pinned joints with different parameters by experimental methods. The effect of the distance from free edge to the diameter of first hole (E/D) ratio, the width of plate to diameter of hole (W/D) ratio and the effect of filler materials on Titanium dioxide (TiO2) and Zinc Sulphide (ZnS) on bearing load are experimentally investigated using laminated woven glass fiber composite plate with single and double serial pinned joints.